GLOBALIZATION AS A FACTOR OF DEINDUSTRIALIZATION IN ECONOMICALLY ADVANCED COUNTRIES - Смаль, Валентина (Human Geography Journal, 2015)
This study analyzes why the economically advanced countries have deindustrialized during the last several decades. Beside such traditional factors of deindustrialization as the steadily rising affluence of consumers in these countries and faster productivity growth in the manufacturing sector relative to other sectors, globalization makes significant contributions to deindustrialization. The paper focuses on the results of direct and indirect effects of globalization on the industrial structure and employment patterns in economically advanced countries.